Bisphenol A induces proliferative effects on both breast cancer cells and vascular endothelial cells through a shared GPER-dependent pathway in hypoxia. (December 2017) - Xu, Fangyi; Wang, Xiaoning; Wu, Nannan; He, Shuiqing; Yi, Weijie; Xiang, Siyun; Zhang, Piwei; Xie, Xiao; Ying, Chenjiang
Abstract: Based on the breast cancer cells and the vascular endothelial cells are both estrogen-sensitive, we proposed a close reciprocity existed between them in the tumor microenvironment, via shared molecular mechanism affected by environmental endocrine disruptors (EDCs). In this study, bisphenol A (BPA), via triggering G-protein estrogen receptor (GPER), stimulated cell proliferation and migration of bovine vascular endothelial cells (BVECs) and breast cancer cells (SkBr-3 and MDA-MB-231) and enhanced tumor growth in vivo. Moreover, the expression of both hypoxia inducible factor-1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF) were up-regulated in a GPER-dependent manner by BPA treatment under hypoxic condition, and the activated GPER induced the HIF-1α expression by competitively binding to caveolin-1 (Cav-1) and facilitating the release of heat shock protein 90 (HSP90). These findings show that in a hypoxic microenvironment, BPA promotes HIF-1α and VEGF expressions through a shared GPER/Cav-1/HSP90 signaling cascade. Our observations provide a probable hypothesis that the effects of BPA on tumor development are copromoting relevant biological responses in both vascular endothelial and breast cancer cells. Graphical abstract: Highlights: BPA promotes biological responses in endothelial cells and breast cancer cells. BPA promotes HIF-1α expression via protein-protein interaction involving GPER/Cav-1/HSP90. BPA serves as a possible contributing factor for mammary cancer in hypoxic microenvironment.